Hydrodynamic Effect On Low Field Gradient Magnetophoresis Of Superparamagnetic Nanoparticles - Leong, Sim Siong (2017)
Two-ways momentum transfer between moving magnetic nanoparticles (MNPs) and surrounding fluid (which is known as hydrodynamic effect) has been revealed to portray a vital role in low field gradient magnetophoresis conducted under microfluidic system. However, the effect of hydrodynamic on dynamical behavior of macroscopically scaled low gradient magnetic separation (LGMS) still remains unexplored even through it is particularly crucial in the design and optimization of magnetic separator for engineering applications. Therefore, it is the main purpose of this study is to understand the underlying mechanism of LGMS, especially to demonstrate the effect of hydrodynamic, and develop mathematical model to depict the dynamical behavior of this process. Evidently, magnetophoresis induced convective flow, which is resulted from hydrodynamic effect, was generated in MNP solution (even at very low particle concentration of 5 mg/L) subjected to low gradient magnetic field (<100 T/m) and significantly affects separation kinetics of it. Such induced convection is analogous to the natural convection found in heat transportation and can be characterized by the newly defined magnetic Grashof number. The analysis on magnetic Grashof number reveals that induced convection is only absent when particle concentration is below 0.05 mg/L. The intervention of hydrodynamic effect in LGMS has led to the two following phenomena: (1) the continuous homogenization of the MNP solution and (2) accompanying sweeping flow (convective velocity of 10-5 to 10-4 m/s was induced) that accelerates the collection of MNP (13 times fastercompared to the case without convection). Additionally, separation kinetics of hydrodynamically driven LGMS is solely controlled by the magnetic field gradient at the surface adjacent to the magnet (denoted as the “collection plane of particles” in this work) as well as the area of this surface and is independent of the magnetic field distribution across the solution. Also, the separation mechanism of LGMS can be classified according to the range of three dimensionless quantities (Reynold number